2019
DOI: 10.1088/1757-899x/564/1/012096
|View full text |Cite
|
Sign up to set email alerts
|

Industrial processes efficiency and lower energy consumption initiatives through advanced retrofitting in the wood industry

Abstract: In a modern manufacturing system for furniture production, raw material and material, energy and information flows are directly interconnected to obtain competitive products while increasing the productivity, profitability and environmental performance of the enterprise. In the wood industry manufacturing system, raw wood undergoes physical and biological transformation processes (drying and transformation of the biological properties of wood) as well as disruptive actions that are compensated by the order qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…In three additional cases, cooperation with companies is at least noteworthy (Tiwari et al, 2020;Yang and Feng, 2008;Zhu et al, 2007). The majority of publications are peer-reviewed journal papers or part of conference proceedings; exceptions are Ndikumana (2019), Pampanelli et al (2015 and Wills (2009). Nevertheless, the authors of this paper concluded that there are no reasons for the exclusion of specific sources.…”
Section: Search Filtermentioning
confidence: 84%
“…In three additional cases, cooperation with companies is at least noteworthy (Tiwari et al, 2020;Yang and Feng, 2008;Zhu et al, 2007). The majority of publications are peer-reviewed journal papers or part of conference proceedings; exceptions are Ndikumana (2019), Pampanelli et al (2015 and Wills (2009). Nevertheless, the authors of this paper concluded that there are no reasons for the exclusion of specific sources.…”
Section: Search Filtermentioning
confidence: 84%
“…Together with a chaotic warehouse system and an automated labelling unit, they form an efficient production cell suitable for companies involved in piece production. The development of standardisation and seriality causes the transfer of furniture production from small workshops to large units [39].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of Industry 4.0 is to create a model in which new technologies and workers interact and create an intelligent and efficient environment [38]. In a modern furniture production system, the flows of raw materials and materials, energy and information are directly linked to the aim of producing competitive products while increasing productivity, profitability and environmental performance [39]. Industry 4.0 consists of three main features that have been described in several studies [5,40], which consist of three different types of integration that are expected to fill the production network in the future [41,42], namely, the vertical, horizontal and complete technical integration [31].…”
Section: Integration Of Industry 40 Into Smart Factoriesmentioning
confidence: 99%